Experimental study on the mechanical behavior and failure mechanism of 3d MWK carbon/epoxy composites under quasi‐static loading. Issue 12 (30th April 2015) - Li, Dian‐Sen; Xia, Yong; Zhou, Qing; Jiang, Lei; Jiang, Nan
Abstract : Quasi‐static tensile, out‐of compression, in‐plane compression, three‐point‐bending and shear tests were conducted to reveal the mechanical behavior and failure mechanisms of three‐dimensional (3D) multiaxial warp‐knitted (MWK) carbon/epoxy composites. The characterization of the failure process and deformation analysis is supported by high‐speed camera system and Digital Image Correlation. The results show that tensile, bending, out‐of‐plane compression, in‐plane compression stress–strain response exhibit obvious linear elastic feature and brittle fracture characteristics, whereas the shear response exhibits a distinct nonlinear behavior and gradual damage process. Meanwhile, 3D MWK carbon/epoxy composites have good mechanical properties, which can be widely used in the fields of engineering. In addition, the failure for tension behaves as interlayer delaminating, 90/+45/−45° interface debonding and tensile breakage of 0° fibers; the damage for out‐of‐plane compression is mainly interlaminar shear dislocation together with local buckling and shear fracture of fibers; the failure pattern for in‐plane compression is 90° fiber separating along fiber/matrix interface as well as 0/+45/−45° fiber shear fracture in the shear plane. The main failure for bending is fiber/matrix interface debonding and fibers tearing on the compression surface, 0° fibers breakage on the tension surface as well as fiber layers delaminating. Although the shear behavior is characterized by a gradually growing shear matrix damage, 90/+45/−45° interface debonding, +45/−45° fibers shear fracture, and final 0° fiber compression failure. POLYM. COMPOS., 37:3486–3498, 2016. © 2015 Society of Plastics Engineers